2018
DOI: 10.4132/jptm.2018.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Features That Differentiate Follicular Neoplasm from Mimicking Lesions

Abstract: BackgroundIt is difficult to correctly diagnose follicular neoplasms (FNs) on fine-needle aspiration cytology (FNAC) because it shares many cytological features with other mimicking lesions. The aim of this study was to identify the cytological features that differentiate FNs from mimicking lesions. MethodsWe included the cytological slides from 116 cases of thyroid FN diagnosed on FNAC, and included their subsequent histological diagnoses. We evaluated the cytological architectural pattern and nuclear feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…The compatibility rate with histopathology of Han K et al in the FN/SFN series of 116 cases were only 44%. Incompatible lesions were 40% TPC and 15% NG in this FN / FNK series (21). The compatibility rate in this study was 36% in the FN/SFN series while incompatible lesions were 30% PTC+PTMC and 33% NG in the our FN/SFN group.…”
Section: Discussionsupporting
confidence: 41%
“…The compatibility rate with histopathology of Han K et al in the FN/SFN series of 116 cases were only 44%. Incompatible lesions were 40% TPC and 15% NG in this FN / FNK series (21). The compatibility rate in this study was 36% in the FN/SFN series while incompatible lesions were 30% PTC+PTMC and 33% NG in the our FN/SFN group.…”
Section: Discussionsupporting
confidence: 41%
“…Currently, TBSRTC DC IV (SFN) is recommended for nodules that are at least moderately cellular and show prominent architectural alteration including cellular crowding, microfollicles, and dispersed isolated cells [ 1 , 2 ]. Nevertheless, many researchers have reported poor cytohistologic correlation of DC IV (SFN) [ 22 , 27 , 30 33 ].Up to 44% of the nodules of which the cytologic features were concordant with DC IV (SFN), turned out to be non-neoplastic lesions [ 27 ], implying that diagnosing follicular-patterned neoplasms remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, microfollicles were sometimes arranged in trabecular or branching pattern, which was more frequently identified in FTCs (40.0%) than FAs (15.2%). Han et al have also described that this trabecular pattern was more commonly observed in FAs and FTCs than in nodular hyperplasia although the frequency did not differ between FAs and FTCs [ 22 ]. Further evaluation in a larger cohort is required to elucidate the significance of this unique pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this method is applicable only to PTC. Identifying other types of DTC (FVPTC, FTC, and HTC) is hampered by a lack of distinguishing cytological characteristics in ultrasound images ( Figure 1 ), such as hypo-echogenicity, irregular margins, or microcalcifications [ 10 ]. In many cases, surgical resection of the tumor is necessary to confirm DTC subtypes, such as FTC and HCC.…”
Section: Introductionmentioning
confidence: 99%